Variable geometry gas turbine performance analysis. - Cleverson Bringhenti (2003)
Gas turbines are optimised at design point. When they operate at off-design, the performance is poor because the blade passages are not adequate for the new flow conditions. In order to improve part-load performance, it is necessary to re-shape the blade passages. This can be done with blade re-staggering. Engines with this capability are called variable geometry engines.This work aims at the development of appropriate methodologies to numerically investigate the influence of the main engine components (compressor, turbine and propelling nozzle) on engine performance, as a mean to support applications of high performance cycles that demand extreme operating conditions.An investigation of variable geometry compressor and turbine stators was carried out by means of synthesizing their performance maps at many stator blade settings and the use of such information in cycle analysis. To support the huge amount of calculations required for off-design analysis, a computer program has been developed.Validation of the methodology was performed using data available in the open literature. A powerful tool for the gas turbine simulation that had proved to produce quality results is made available to support research on new concepts for high performance cycles.